Evaluasi Penerapan Manajemen Teknologi Informasi Menggunakan Cobit Pada Unit Arsip IPB - A.Muh.Yakin Amin; Irman Hermadi; Yani Nurhadryani3 Yani Nurhadryani (Jurnal Pustakawan Indonesia, 2016)
Community College of popular as the academic community. Administrative activities in universities can not be separated from the recording of incoming and outgoing mail, file reception and file delivery. The archiving process as an important record of the history of the institution, for easy access and collection of data, synthesize information and improve the utilization of archives. Application of Information Technology (IT) is essential to the use and development of IT for the better in the service of the administration of the university. IPB Archives Unit has been using Dynamic Archival Information System (SIKD) and Static Archival Information System (SIKS) to serve the management of governance archiving. However, the use of information systems used by the Archives Unit IPB unknown level governance capabilities within IT management. Therefore this study to evaluate the capability of IT management level in the management of archives using the framework Control Objectives for Information and related Technology (COBIT). Selection of COBIT framework because it has many advantages one of them as a control tool facilitates business requirements development of Standard Operating Procedures (POB) and provide recommendations to improve management of the management. Domain of COBIT process selected after the mapping with the goal of IPB Archives Unit. The results of the mapping created a questionnaire. Questionnaires were administered to respondents who manage the archiving process on IPB Archives Unit. The data obtained were processed to determine the level of capability IPB Archives Unit. The results obtained from this study indicate that the Archives Unit IPB capability criteria are at level 1 (performed process) to the percentage of votes the capabilities of the application of best practice IT management is at Capability Level L (Largely Achieved).Keywords: Capability Level, COBIT, SIKD, SIKS, IPB Archives Unit